2005
DOI: 10.1042/bj20041899
|View full text |Cite
|
Sign up to set email alerts
|

Decreased lipid efflux and increased susceptibility to cholesterol-induced apoptosis in macrophages lacking phosphatidylcholine transfer protein

Abstract: Macrophages are the predominant cellular component of atherosclerotic lesions, where they scavenge oxidatively modified lipoproteins while defending themselves against cholesterol-induced cytotoxicity by adaptive mechanisms that depend in part on the synthesis, distribution and efflux of phosphatidylcholines. PC-TP (phosphatidylcholine transfer protein) is a START (steroidogenic acute regulatory protein-related lipid transfer) domain protein that catalyses the intermembrane transfer of phosphatidylcholines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…L'analyse phylogénétique montre que les protéines à domaine START se distinguent plus par leur spécificité vis-à-vis du STARD2 est une protéine cytoplasmique qui promeut l'échange rapide de la phosphatidylcholine (PC) supposément de son lieu de synthèse vers la face interne de la membrane plasmique et/ou la membrane externe de la mitochondrie. STARD2 serait responsable du remplissage de la membrane plasmique par de la PC en réponse à l'efflux de phospholipides vers les lipoprotéines plasmatiques de type HDL (high density lipoproteins) au cours du transport des HDL entre les tissus [17,18]. In vitro, STARD10 permet l'échange membranaire de PC et PE [14].…”
Section: Le Domaine Start Un Domaine Conservé Chez Les Pluricellulairesunclassified
“…L'analyse phylogénétique montre que les protéines à domaine START se distinguent plus par leur spécificité vis-à-vis du STARD2 est une protéine cytoplasmique qui promeut l'échange rapide de la phosphatidylcholine (PC) supposément de son lieu de synthèse vers la face interne de la membrane plasmique et/ou la membrane externe de la mitochondrie. STARD2 serait responsable du remplissage de la membrane plasmique par de la PC en réponse à l'efflux de phospholipides vers les lipoprotéines plasmatiques de type HDL (high density lipoproteins) au cours du transport des HDL entre les tissus [17,18]. In vitro, STARD10 permet l'échange membranaire de PC et PE [14].…”
Section: Le Domaine Start Un Domaine Conservé Chez Les Pluricellulairesunclassified
“…In a study of mouse peritoneal macrophages from Pctp 2/2 and wild-type mice, we observed that the absence of PC-TP expression increased the susceptibility of macrophages to apoptotic, but not necrotic, cell death in response to loading with unesterified cholesterol (6). The influence of macrophage apoptosis on atherosclerosis is dependent on a balance of apoptosis and phagocytosis (22,23).…”
Section: Discussionmentioning
confidence: 98%
“…PC-TP (also known as StarD2) is a member of the steroidogenic acute regulatory-related lipid transfer (START) domain protein superfamily (3). It is expressed in a variety of tissues and is enriched in liver (1,4,5) and macrophages (6). Although PC-TP promotes the exchange of phosphatidylcholine between membranes in vitro (1), its biological function remains elusive.…”
mentioning
confidence: 99%
“…Other LysM-cre specifi c crosses were done for the PCTP (StARD2) protein, whose initial lipid phenotype was unclear. In this case, macrophage specifi c deletion of PCTP resulted in decreased cholesterol effl ux to ApoA-I particles ( 34 ). It is possible that StARD4 might play an important role in the development of atherosclerosis by infl uencing macrophage cholesterol effl ux.…”
Section: Discussionmentioning
confidence: 99%